Removal of heavy metals in a wet detention pond in Reykjavik - Guðbjörg Esther G. Vollertsen 1983-; Hrund Ólöf Andradóttir 1972-; Hildur Ingvarsdóttir 19-- (2009)
A wet detention pond draining a residential area in the outskirts of Reykjavik was monitored during a 12 month period starting June 1st, 2008. The goal of the project was to increase the local information on stormwater pollution and detention pond treatment efficiency. Water samples taken during five runoff events were analyzed for a range of heavy metals and particle size. The results of this study was that on average, the heavy metal content of residential surface runoff entering the Icelandic pond was low compared to ponds in similar catchments in other northern countries. The highest pollutant concentrations occurred during snowmelt and in rain events preceding a long dry period. First flush of heavy metals was observed in almost all the surface runoff events but the extent of the first flush varied between metals. Chromium, copper and nickel were found to be mainly (>50%), bound to particulates whereas zinc was <40 % particulate bound. The mean particle diameter in the inflowing runoff ranged from 10-20 μm and 68 % of the mass was bound to particles less than 20 μm. Despite the low pollution concentration in the inflowing water, the total treatment efficiency of the pond calculated based on the Event Mean Concentration (EMC) was found to be relatively high, or in the 80-90% range. Reykjavík Energy Environment and Energy Research Fund and the University of Iceland Research Fund